From rhetoric to reality: advancing literacy by cross-curricular means - Alexander, Joy; Walsh, Patrick; Jarman, Ruth; McClune, Billy (The Curriculum Journal, 2008)
Cross-curricularity, literacy and critical literacy are currently promoted as components of a curriculum appropriate for the twenty-first century. The first two, in particular, are prescribed elements of classroom experience in Northern Ireland, which is the immediate context of this article, but also more widely in the UK. Teachers are implementing cross-curricular and interdisciplinary initiatives, but rhetorical imperatives can translate into superficial realities. The reasons for this are explored, as are the reasons why interdisciplinary studies, literacy across the curriculum and critical literacy are deemed to be of significance for education at the present time. The ‘Making Science: Making News’ project is described, in which Key Stage 3 science and English classes worked together, with input from a research scientist and a journalist, to produce articles on space science which were published in local newspapers. The outcomes of the project are discussed from the perspectives of both teachers and learners. It is argued that this project is an example of genuine interdisciplinary activity; that it went beyond literacy skills to a deeper development of scientific discourse; and that, through its media connection, there was potential for building an ongoing awareness in pupils of critical literacy and scientific literacy.